2016
DOI: 10.3390/jcm5020017
|View full text |Cite
|
Sign up to set email alerts
|

Role of EMT in Metastasis and Therapy Resistance

Abstract: Epithelial–mesenchymal transition (EMT) is a complex molecular program that regulates changes in cell morphology and function during embryogenesis and tissue development. EMT also contributes to tumor progression and metastasis. Cells undergoing EMT expand out of and degrade the surrounding microenvironment to subsequently migrate from the primary site. The mesenchymal phenotype observed in fibroblasts is specifically important based on the expression of smooth muscle actin (α-SMA), fibroblast growth factor (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
311
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(323 citation statements)
references
References 123 publications
(172 reference statements)
11
311
0
1
Order By: Relevance
“…According to progression of cancer, cancer cells seems to acquire the ability of invasion and metastasis by EMT (24). Several studies already suggested that Wnt signaling pathway closely related to EMT (25,26), and EMT related factors would be prognostic factors of ESCC (27,28). These studies support the hypothesis that the canonical Wnt signaling pathway activates the progression and metastasis of ESCC through the EMT; whether Wnt3a expression might also be correlated with the progression and metastasis of ESCC should be investigated.…”
Section: Discussionsupporting
confidence: 68%
“…According to progression of cancer, cancer cells seems to acquire the ability of invasion and metastasis by EMT (24). Several studies already suggested that Wnt signaling pathway closely related to EMT (25,26), and EMT related factors would be prognostic factors of ESCC (27,28). These studies support the hypothesis that the canonical Wnt signaling pathway activates the progression and metastasis of ESCC through the EMT; whether Wnt3a expression might also be correlated with the progression and metastasis of ESCC should be investigated.…”
Section: Discussionsupporting
confidence: 68%
“…49,50 Many evidences demonstrated that EMT contributes to cancer progression, metastasis, tumor microenvironment crosstalk, and drug resistance. 51,52 EMT-induced cancer cells have been changed a lot at the molecular level and display increased expression of mesenchymal genes (fibronectin, N-cadherin, and vimentin) and decreased expression of epithelial genes (E-cadherin and ZO-1). 52,53 In many cases, gain of N-cadherin and loss of E-cadherin are unique features of EMT.…”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…It is now well known that EMT is a physiological cellular mechanism that tumor cells borrow during the metastatic process. In this way, in many human cancers, the HGF/cMET pathway participates in malignant progression and cell scattering, invasion, and protection from apoptosis, and in metastasis formation [Fujita and Sugano, 1997;Samamé Pérez-Vargas et al 2013;Smith and Bhowmick, 2016].…”
Section: Molecular Heterogeneity Of Colorectal Cancermentioning
confidence: 99%